Evaluasi Kinerja Konsultan terhadap Manajemen pada Pekerjaan Ruas Jalan Lambaro - Pidie - Fatimah, Aldina; Habibie, Teuku; Hayati, Kemala; Zainuddin, Zainuddin (Tameh, 2022)
The development project on the Lambaroe-Pidie national road is expected to be carried out according to plan. This can be realized with the role of a team of Project Management Consultants within the Aceh National Road Implementation Center who carry out construction management including implementation and control in program preparation, technical planning, construction implementation and supervision, quality control, service and supply of materials and equipment. The purpose of this research is to evaluate the factors that determine the effective performance of consultants and evaluate the performance indicators of consultants on management on the Lambaroe-Pidie national road section. The research method is a mixed method, which is a method that combines qualitative and quantitative methods. The sampling technique used is quotas. This research was conducted by distributing questionnaires to the owner, project officer, PT. Citra Diecona, Contractors and Technical Assistance Team (Bantek) with a total of 13 respondents. Questionnaire tests include validity tests and reliability tests. Based on the results of the study, the validity test obtained a value of Rcount > Rtable with a value of 0.552, this indicates that the question item is valid. In the reliability test, a value of 0.694 was obtained, this indicated that the respondents' answers were reliable. Based on the results of the descriptive analysis the initiative variable (X5) has the highest value of 4.692, this explains that the respondents are very satisfied with the consultant's performance on the initiative aspect. The ability to communicate (X2) has the lowest value with a mean value of 4.369. although this variable has the lowest mean, the results of the study show that respondents are satisfied with the consultant's performance on the communication aspect. The evaluation of the consultant's performance on management on the Lambaro - Pidie road section has met the road performance indicators in accordance with the 2017 Public Works Regulations concerning road performance indicators on management on the Lambaro - Pidie National Road section.